A safety evaluation of budesonide MMX for the treatment of ulcerative colitis. Issue 4 (3rd April 2018) - Bezzio, Cristina; Festa, Stefano; Zerboni, Giulia; Papi, Claudio; Manes, Gianpiero; Saibeni, Simone
ABSTRACT: Introduction : Budesonide belongs to low-bioavailability steroids class. A novel oral formulation of budesonide, which uses the Multi-Matrix System (MMX) for delivering drugs to the colon, is now available as a possible treatment of ulcerative colitis patients intolerant or not-responding to first-line therapy with 5-ASA. Areas covered : in this review we present information about the development and the use of budesonide MMX and we provide data about its mechanism of action as well as, pharmacodynamics and pharmacokynetics. Moreover, we present the available literature data about the efficacy and, mainly, the safety of budesonide-MMX. Expert opinion : budesonide-MMX is a new therapeutic option in mild-to-moderate UC patients. Its good safety profile in clinical trials undoubtedly represents a strength for a possible wide use in clinical practice, mainly if it will be confirmed by post-marketing data. Other indications, such as treatment of colonic Crohn's disease, could theoretically be considered, if sustained by reliable scientific data.